PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN BUDAYA KEWIRAUSAHAAN UNTUK MENGURANGI PENGANGGURAN DAN KEMISKINAN - Maisaroh, Siti; Sukhemi, S (JEJAK: Jurnal Ekonomi dan Kebijakan, 2011)
The purpose of this study to identify and seek answers through the establishment of community empowerment model in order to reduce unemployment and poverty.The research was conducted in District Dlingo Bantul, especially in the Village Muntuk. The method of research is conducted with sample survey methods, namely the households respondent sample of the poor and unemployed citizens voted in the village. Data analysis in this study is more designed in the form of qualitative descriptive analysis and SWOT analysis model. The study identified several strategic fundamental potential and central issues as the capital base in the formation of citizens empowerment model, namely: the still high social capital, productive work ethic, the local potential (bamboo handicraft business), technical factors, human capital, productive and entrepreneurial culture. Besides institutional characteristics and conditions of social, economic, cultural and political communities remain conducive and good interaction with various national and local government programs, so it can be a major contributing factor in the formation of community empowerment model in order to solve the problems of unemployment and poverty independently and sustainable. The existence of common perception of the strength and support of stakeholders from sub village, village and district to empower entrepreneurial culture of the residents. Thus, it is recommended the assistance and review of the action also further research and analysis. Assistance is needed only at the beginning of the establishment of the implementation of citizen empowerment model for more effective, efficient and easily applied of model implementation, so that in the future can be done independently and sustainable.